A flag worth dying for : the power and politics of national symbols - Marshall, Tim, 1959- (Scribner, 2017)
Shares insights into the symbolism and power of flags representing the beliefs of nations and non-state organizations, revealing how flags and the politics they represent unite and divide world populations.